Rancang Bangun Sistem Pencampur Minuman Jamu Otomatis Berbasis Mikrokontroler - Ratna Aisuwarya; Nurul Fatimah (Universitas Andalas, 2019)
People in general have a desire to live a healthy life. One way to keep health is by consuming herbal drinks, one of them is known as jamu. Jamu which is commonly found is